Americanismo e antiamericanismo : o ensino de inglês no Brasil de 1931-1951 - Gomes, Rodrigo Belfort (2019)
The aim of this thesis is to investigate the trajectory of English language teaching in Brazil between 1931 and 1951, beginning with the institutionalization of the Direct Method and taking into consideration the concepts of Americanism and anti-Americanism. In order to achieve this, it was necessary to study the educational legislation, U.S. policies in Brazil and newspapers from the time period. It was also necessary to conduct an analysis of the content of the English textbooks, paying special attention to their degree of compliance with the Direct Method and educational law, in a moment that saw both the expansion of English language teaching and the increasing cultural, political and economic interference of the United States. The research conducted for this study took place at NUDOM and at the National Library of Rio de Janeiro, as well as in digital collections of Brazilian and foreign libraries, primarily in books intended to teach the English language published between 1931 and 1951. Newspapers from this period housed in the Digital Library of the National Library were also analyzed. This study ultimately revealed the inclusion of some points of the Direct Method in the English textbooks of the 30s and 40s, as well as several mentions of this method in advertisements and articles in newspapers from the time period. In addition to these findings, it became clear that there was also great difficulty in breaking with secular practices, such as the deductive teaching of grammar and the use of translation. A strong American presence was observed in actions on many fronts that strengthened the teaching of the English language in Brazil, despite the feelings of repulsion on the part of the population, which can be seen in the lyrics of several samba songs that were critical of the United States’ interference in Brazil. This anti-Americanism sentiment, however, was unable to prevent the advancement of English language teaching in Brazil.